Exploring the Role of Public-Private Partnerships in the Development of Multi-Modal Transport Networks in Nigeria: An Operations Research Approach - I, Adaji; M. O., Francis; J. U. , Okeme; G. O, Ijiebor (International Journal of Advanced Mathematical Sciences, 2025)
The development of efficient multi-modal transport networks is critical for enhancing mobility and fostering economic growth in Nigeria. Public-Private Partnerships (PPPs) have emerged as a key strategy for mobilizing private sector investment and expertise in transportation infrastructure projects. This paper explores the role of PPPs in the development of multi-modal transport networks in Nigeria, employing a rigorous operations research approach to analyze the efficiency, risk allocation, and financial feasibility of various PPP models. Using case studies and a mathematical modeling framework, the paper investigates how PPPs can optimize the performance of transport networks, improve service delivery, and address Nigeria’s unique challenges in infrastructure development. The findings suggest that while PPPs offer significant benefits, careful consideration of institutional frameworks, risk management strategies, and financing structures is crucial to their success.